2021
DOI: 10.1111/cea.13965
|View full text |Cite
|
Sign up to set email alerts
|

ADRB2 haplotypes and asthma exacerbations in children and young adults: An individual participant data meta‐analysis

Abstract: Background The polymorphism Arg16 in β2‐adrenergic receptor (ADRB2) gene has been associated with an increased risk of exacerbations in asthmatic children treated with long‐acting β2‐agonists (LABA). However, it remains unclear whether this increased risk is mainly attributed to this single variant or the combined effect of the haplotypes of polymorphisms at codons 16 and 27. Objective We assessed whether the haplotype analysis could explain the association between the polymorphisms at codons 16 (Arg16Gly) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
4
0
2
Order By: Relevance
“…However, the results of various reports are not completely consistent. For example, Karimi L et al found that the polymorphism of Arg16Cly and GI27Glu loci of the ADRB2 gene is related to asthma susceptibility (17). Zhang YQ et al also believed that the polymorphism of the Arg16Cly locus of the ADRB2 gene may be a determinant of asthma severity and response to salbutamol (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of various reports are not completely consistent. For example, Karimi L et al found that the polymorphism of Arg16Cly and GI27Glu loci of the ADRB2 gene is related to asthma susceptibility (17). Zhang YQ et al also believed that the polymorphism of the Arg16Cly locus of the ADRB2 gene may be a determinant of asthma severity and response to salbutamol (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Adrb2 exerts antiinflammatory effects. [35][36][37] Thus, we deduced that ES caused the release of NE from SchG, and NE decreased inflammation after tendon injury through Adrb2.…”
Section: The Anti-inflammation Of the Tendons After Stimulationmentioning
confidence: 99%
“…Передусім шанси реалізації генетично-детермінованої патології оцінюються з обов'язковим урахуванням впливу довкілля. Адже для кожного етнічного поселення, клімато-географічних параметрів місця проживання, особливостей харчових вподобань, частоти близько родинних шлюбів, культури ведення сільського господарства, темпів урбанізації тощо, частота мутантних, мажорних, мінорних алелів є різною [10,11,16,21]. Саме цим і пояснюється різна частота окремих спадково обумовлених хвороб у різних частинах світу.…”
Section: вступunclassified